Maternal perception of their child's nutritional status at less than three years old - Luciane Simões Duarte; Elizabeth Fujimori; Áurea Tamami Minagawa Toriyama; Claudia Nery Teixeira Palombo; Patrícia Pereira Lima Miranda; Ana Luiza Vilela Borges
Abstract OBJECTIVE Assessing maternal perception of their children's nutritional status and identifying associated factors. METHODS A cross-sectional study conducted in a small municipality with 342 children less than 3 years of age treated in Basic Health Units of São Paulo. Nutritional status was classified in percentiles of body mass index for age and maternal perception was assessed using the scale of verbal descriptors (very thin, thin, healthy weight, fat, very fat). Logistic regression was used to identify the associatedfactors. RESULTS 44.7% of maternal perception was found to beinadequate. Mothers of overweight (OR = 11.8, 95% CI: 6.4-21.7) and underweight (OR = 5.5; 95% CI: 1.9-16.2) children had a higher chance of having inadequate perception, similar to mothers of children over 24 months of age (OR = 2.9; 95% CI: 1.4-6.0). CONCLUSION For effective child care in primary care, healthcare professionals should consider maternal perception and helpmothers to identify the nutritional status of children in childcare consultations and growth monitoring.